2015
DOI: 10.1002/mrd.22482
|View full text |Cite
|
Sign up to set email alerts
|

­Changes in the osmolarity of the embryonic microenvironment induce neural tube defects

Abstract: Many maternal disorders that modify the embryonic microenvironment, such as a change in osmolarity, can affect development, but how these changes influence the early embryo remains obscure. Neural tube defects, for example, are common congenital disorders found in fetus and neonates. In this study, we investigated the impact of anisotonic osmolarity (unequal osmotic pressures) on neural tube development in the early chick embryo, finding that neuronal cell differentiation was impaired in the neural tube due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…However, we found the neural tube of this level re-open in the experimental groups on the 4.5 day. This phenotype is similar with the high-salt treated chick embryos in our previously study (Jin et al, 2015). Thus, we speculated that the opening of the neural tubes was related to the abnormal cell proliferation and apoptosis, so that we performed PCNA and Tunel staining.…”
Section: Discussionsupporting
confidence: 83%
“…However, we found the neural tube of this level re-open in the experimental groups on the 4.5 day. This phenotype is similar with the high-salt treated chick embryos in our previously study (Jin et al, 2015). Thus, we speculated that the opening of the neural tubes was related to the abnormal cell proliferation and apoptosis, so that we performed PCNA and Tunel staining.…”
Section: Discussionsupporting
confidence: 83%
“…This represents one kind of strength and a weakness of the model. In our previous study, we demonstrated that chick embryos exposed to excess salt have impaired retina and lens development (Chen et al, 2014) and induced neural tube defects (Jin et al, 2015). Here, we investigate the adverse impact of high-salt-induced hyperosmolarity on cardiovascular development using early chick embryos.…”
Section: Introductionmentioning
confidence: 94%
“…The eggs were incubated in a humidified incubator (Yiheng Instrument, Shanghai, China) at 38°C and 70% humidity. After 36 h of incubation, the chick embryos were treated as previously described (Chen et al, 2014;Jin et al, 2015): in brief, 2 ml albumen was removed from an egg and the egg was then injected with 500 µl of three different concentrations of NaCl. For the control group, we injected 0.7% NaCl (calculated final osmolality of the egg was 240 mosm l −1 ); for the 300 mosm l −1 group, we injected 16.85% NaCl (calculated final osmolality of the egg, 300 mosm l −1 ); for the vitamin C (VC) rescue experiment , we administered VC (0.5 mg egg −1 ) after injection of 16.85% NaCl.…”
Section: Chick Embryosmentioning
confidence: 99%
“…Bone morphogenetic protein (BMP) signaling and Sonic hedgehog (Shh) signaling jointly regulate the formation of DHLP, subsequently affecting the closure neural tube [42]. Neural tube development is highly dependent on the precisely spatiotemporal regulation of bone morphogenetic protein 4 (BMP4), paired box 7 (Pax7) and Sonic hedgehog (Shh) genes in the dorsal side of the tube [43]. After exposure to OA, the inhibition of BMP4and Shh expression in the dorsal neural tube suggests that OA exposure could also affect the formation of DHLP, and then disturb the subsequent folding process, and ultimately lead to the incomplete closure of the neural tube.…”
Section: Discussionmentioning
confidence: 99%